(-)-Stepholidine reduces cue-induced reinstatement of cocaine seeking and cocaine self-administration in rats. (1st August 2018) - Manuszak, M.; Harding, W.; Gadhiya, S.; Ranaldi, R.
Highlights: (-)-Stepholidine reduces cue-induced reinstatement of cocaine seeking. (-)-Stepholidine reduces cocaine self-administration/reward. (-)-Stepholidine may have potential as an anti-cocaine relapse treatment. Abstract: Background: Dopamine receptors are implicated in cocaine reward and seeking. We hypothesize that (-)-stepholidine, a dopamine D1/D2/D3 multi-receptor agent, would be effective in reducing cocaine reward and seeking in an animal model. We investigated the effects of (-)-stepholidine in cue-induced reinstatement of cocaine seeking and cocaine self-administration (reward). Methods: Cue-induced reinstatement experiment: Rats were trained to press a lever reinforced by cocaine (1 mg/kg/injection) for 15 consecutive daily sessions, after which the response was extinguished by withholding cocaine and cocaine-paired cues (light and pump activation). This was followed by a cue-induced reinstatement test where subjects were exposed to two cocaine cue presentations and presses on the active lever produced cues. Subjects were treated with one of four (-)-stepholidine doses prior to the reinstatement test. Cocaine self-administration (reward) experiment: Rats were trained to self-administer cocaine under a progressive ratio schedule of reinforcement. After stable breakpoints were established, rats were injected with four doses of (-)-stepholidine prior to testing; each dose was injected prior to a separate test session with no-treatment sessions intervening to re-establish break points. Results: (-)-Stepholidine significantly reduced cue-induced reinstatement of cocaine seeking in a dose-related manner. Additionally, (-)-stepholidine significantly reduced break points for cocaine reward. (-)-Stepholidine did not significantly affect locomotor activity. Conclusions: (-)-Stepholidine reduces cue-induced reinstatement of cocaine seeking and cocaine reward, suggesting that it may be useful in treating relapse in cocaine addiction.